Examining the Effects of Resilience, Psychological Well-Being, and Self-Efficacy on Students’ Understanding of Accounting - Nurwendari, Weny; Handayani, Silvia Mariah; Hidayat, Taufik; Herliani, Rini (Jurnal Paedagogy, 2026)
This study aims to examine the effects of resilience, psychological well-being, and self-efficacy on students’ accounting understanding. A quantitative explanatory research method was employed. Data were collected from 118 undergraduate students enrolled in the Accounting Education Program, Faculty of Economics, Medan State University. The participants were selected using purposive sampling and had completed core accounting courses. Data were gathered through a structured questionnaire measured on a five-point Likert scale. Data analysis was conducted using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS software. The results demonstrate that resilience, psychological well-being, and self-efficacy have positive and statistically significant effects on accounting understanding. Among these variables, self-efficacy exhibits the strongest influence on accounting understanding (β = 0.41; p < .001), followed by resilience and psychological well-being. The structural model explains 65% of the variance in accounting understanding (R² = 0.65), indicating strong explanatory power. These findings suggest that students’ accounting understanding is influenced not only by cognitive learning processes but also by psychological resources that support academic engagement and persistence.